Menggali Potensi dan Bakat Peserta Didik - Ardiansyah Ardiansyah; Nurul Maulida Alwi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This community service activity aims to assist students in recognizing and developing their potential and talents as a basis for designing future career goals. The implementation of the activity was carried out at SMAN 1 Suwawa by involving class XI students and students as facilitators and counselors. The service was carried out in two main stages, namely a workshop on potential and talent recognition and career counseling sessions. The workshop was conducted through interactive lecture, discussion, and question and answer methods to provide insight into the importance of recognizing interests and talents early on. The next stage is career counseling which aims to facilitate students in exploring career choices based on interest and aptitude tests, interviews, and the preparation of short-term and long-term career plans. The results of the activity showed that students were very enthusiastic about participating in the workshop and were more motivated after recognizing their potential. Meanwhile, the counseling session helped learners understand their professional direction and goals more clearly and structurally. This activity confirms the importance of collaboration between schools, teachers, students, and counselors in building learners' career awareness through self-recognition of their potential since middle school age. Translated with DeepL.com (free version)